Command Secondary School Teachers’ Attitude Towards Information and Communication Technology Facilities for Instruction - Florence Olutunu Daramola (Indonesian Journal of Multidiciplinary Research, 2022)
This study examined command secondary school teachers’ attitudes towards the use of information and communication technology for instruction in Oyo State. The study adopted descriptive research of the survey type. The population for this study comprises all teachers in Command Secondary Schools in Oyo State, Census of all 317 teachers in the three schools was taken as a sample for the study. In addition, a stratified random sampling technique was used to classify teachers based on gender, teachers’ teaching qualification, and teaching experience. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses respectively with the aid of statistical product and service solution (SPSS) version 20.0 at 0.05 level of significance. The results of the findings indicated that command secondary school teachers had a positive attitude towards the utilization of Information and Communication Technology (ICT) tools for instruction and no significant difference exists in the attitude of command secondary school teachers towards the utilization of ICT tools for instruction based on gender, years of teaching experience, and academic qualification. The study concluded that instructional activities can be stimulated and enhanced if appropriate ICT tools are deployed for instruction and positive attitudes are manifested by the teachers. It was therefore recommended that secondary school teachers should be encouraged to deployed ICT tools for instruction irrespective of their gender.